Bearing Characteristics of Surrounding Rock of Deep Mining Roadway with Full and End Bolt Anchorages: A Comparative Numerical and Experimental Study. (16th January 2021) - Shi, Wenbao; Li, Yan; Li, Wanfeng; Li, Shihui
Abstract : The support strength of surrounding rock in deep mining roadways can be significantly improved by replacing the end bolt anchorage with a full one. The support effects of both types of anchorage and the axial stress distribution characteristics in anchored bolt bodies were assessed via the indoor pull-out test, simulated via the FLAC3D software, and verified by field measurements. The stability and variation patterns of the axial force, as well as the evolution law of bearing characteristics of surrounding rock, were analyzed. The results indicate that the polymorphic deformations of deep mining roadway surrounding rock and the bolt support body interact synchronously. The axial force evolution trend in bolt bodies with end anchorage revealed by field tests was consistent with the laboratory test results, in contrast to that of full anchorage. Although stress distribution laws in both sides of the mining roadway were the same for both types of anchorage, the vertical stress peak and damage range of full-anchored surrounding rock slightly exceeded those of the end-anchored one. The anchored area bearing a higher load alleviated the stress concentration of the surrounding rock. Since the deformations in fully and end anchored surrounding rocks increased gradually and sharply, respectively, the full anchorage is more conducive to deformation moving control of deep mining roadway surrounding rock. The research results can provide theoretical guidance for the design and construction of deep mining roadway bolt support.